2012
DOI: 10.7554/elife.00047.012
|View full text |Cite
|
Sign up to set email alerts
|

Author response: DNA-PK is a DNA sensor for IRF-3-dependent innate immunity

Abstract: Innate immunity is the first immunological defence against pathogens. During virus infection detection of nucleic acids is crucial for the inflammatory response. Here we identify DNA-dependent protein kinase (DNA-PK) as a DNA sensor that activates innate immunity. We show that DNA-PK acts as a pattern recognition receptor, binding cytoplasmic DNA and triggering the transcription of type I interferon (IFN), cytokine and chemokine genes in a manner dependent on IFN regulatory factor 3 (IRF-3), TANK-binding kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For instance, studies showed that DNA damage induced by etoposide or by doxorubicin instigates an ATM-dependent but cGASindependent immune response (Luthra et al, 2017;Dunphy et al, 2018). In addition, DNA-dependent protein kinase (DNA-PK) was characterized as another DNA sensor contributing to IFN-I (Ferguson et al, 2012), and more recently, DNA-PK has been suggested to induce a cGAS-STING-independent IFN-I induction upon DNA damage in humans but not in mice, highlighting species differences in immune activation following DNA breaks (Burleigh et al, 2020). Further, DNA-PK antagonizes cGAS activation through inhibition of its catalytic activity.…”
Section: Cgas Independent Activation Of Ifn-i Responsementioning
confidence: 99%
“…For instance, studies showed that DNA damage induced by etoposide or by doxorubicin instigates an ATM-dependent but cGASindependent immune response (Luthra et al, 2017;Dunphy et al, 2018). In addition, DNA-dependent protein kinase (DNA-PK) was characterized as another DNA sensor contributing to IFN-I (Ferguson et al, 2012), and more recently, DNA-PK has been suggested to induce a cGAS-STING-independent IFN-I induction upon DNA damage in humans but not in mice, highlighting species differences in immune activation following DNA breaks (Burleigh et al, 2020). Further, DNA-PK antagonizes cGAS activation through inhibition of its catalytic activity.…”
Section: Cgas Independent Activation Of Ifn-i Responsementioning
confidence: 99%
“…DNA protein kinase (DNA-PK) is a protein complex made up of a DNA protein kinase catalytic subunit (DNA-PKcs), ku70, and ku80, and is best known for its role in DNA double stranded break repair. However, several studies have shown that it can bind to transfected DNA and elicit the expression of IFN-β and other ISGs, independent of kinase activity (Ferguson et al, 2012;Harnor et al, 2017;Burleigh et al, 2020). In addition, the Ku70 subunit has also been identified as a possible DNA sensor in studies where plasmid transfected HEK 293 cells produce the type three IFN, IFN-λ1, that can limit HIV replication (Zhang X. et al, 2011).…”
Section: Ddx41 Ku70/dna-pk and Rna Polymerase IIImentioning
confidence: 99%